THE EFFECT OF DIVERSIFICATION LEVEL, NUMBER OF SEGMENTS, AND INDUSTRY SECTOR TYPE ON COMPANY PERFORMANCE - Felicia Hokyani; Rizka Indri Arfianti (Journal of Management and Leadership, 2021)
The high competition in the business world with many competitors has forced the company to develop its business, one of them by diversification. This study aims to investigate the influence of diversification level, the number of segments, and type of industrial sector on firm performance measured by the excess value. The theory underlying this research is agency theory, which describes the relationship between the company owners with the company management. The number samples of this study are 333 companies from the miscellaneous industry sector, consumer goods sector, and basic industry and chemicals sector listed on the Indonesia Stock Exchange throughout 2017 – 2018. The results showed that data can be pooled for 3 years, all classic assumption tests are fulfilled, and partial regression coefficient test found that variable diversification level and the variable number of segments > 0.05, then H01 and H02 rejected, while the type of miscellaneous industry sector and type of consumer goods sector <0.05, then H03 and H04 received. The conclusion showed that variable diversification level and number of segments has not sufficient evidence of a negative effect on excess value, while the type of miscellaneous industry sector and type of consumer goods sector sufficient evidence of a negative effect on excess value.